Optimizing Millennial Farmers' Harvest Results by Maximizing Internet of Things Programs in Lamongan Regency - Emmy Hamidah; Saifuddin Zuhri; Idum Satia Santi; Etty Sri Hertini; Yani Prabowo (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study is a type of qualitative research with a descriptive approach, namely an approach that describes one by one the main topics in this study. The topics in this study are related to Millennial Farmers, the Internet of Things, and agricultural production results used in this study. The data used in this study are secondary data that researchers obtained indirectly through scientific articles, books, magazines, and other sources used in this study. The data obtained were analyzed by stages of data collection, data selection, data reduction, and drawing conclusions with a more complete explanation in the results and discussion sections. Why is it the choice of millennial farmers? Because millennial farmers are the generation that is most sensitive to and literate in technology. In addition, millennial farmers have a longer term to develop compared to previous generations. In addition, why should it be Lamongan district? Because Lamongan is the largest rice contributor in East Java.